Praktik Paradiplomasi dalam Implementasi Kerjasama Smart City Pemerintah Kota Bandung dan Kota Seoul - Renny Candradewi Puspitarini; Fahrisya Tiko Septiarika; Randy Bramastya (Universitas Medan Area, 2021)
Paradiplomacy was popular in the early 1980s, when the Quebec City government strengthened cooperation with regional governments of other countries and other state actors in international relations. This phenomenon was studied in depth by diplomacy experts, namely Duchacek and Soldatos, which was later implemented in practice in transnational relations between countries in the world. The same thing was done by the city government of Bandung. The Bandung City Government undergoes the stages of smart collaboration formulation. An important process in paradiplomacy is the occurrence of communication contained in the policy advocacy process of the Seoul City government through the Knowledge Sharing Program (KSP) under the Ministry of Economy and Finance of South Korea. This study aims to see the Bandung City government as a subnational government entity conducting diplomacy outside the context of traditional diplomacy, namely paradiplomacy in implementing Smart City cooperation with the City of Seoul in 2016-2019. This research was conducted using a qualitative approach with literature study methods. The literature study method is useful for gathering secondary information needed to support findings in research. This study produces a map of cooperation between the City of Seoul and the City of Bandung which has not been discussed in a similar study using a paradiplomation framework that combines the concepts of Duchacek, Soldatos and Keohane. The cooperation map referred to is an in-depth explanation of the smart city of Bandung which includes Smart Branding, Smart Living, Smart Environment and Smart Government.